Environmental Communication in West Sulawesi: The Role of Media and Technology in Nature Conservation Campaigns - Rusnali, Andi Nur Aisyah; Bahfiarti, Tuti; Mau, Muliadi; Faried, Muhammad (Palakka : Media and Islamic Communication, 2024)
This research aims to analyze the role of media and technology in nature conservation campaigns in West Sulawesi and their impact on increasing environmental awareness in local communities. The main focus of the research is how mass media and digital technology are used as ecological communication tools to disseminate information, increase public participation, and encourage behavioral changes in maintaining rich and diverse local ecosystems. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with stakeholders, including government officials, environmental activists, local communities, and media and technology practitioners. In addition, content analysis was carried out on ecological campaigns distributed through various media platforms, such as television, radio, and social media, as well as environmental-based technology applications. The research results show that media and technology play a significant role in driving the nature conservation campaign in West Sulawesi. The use of social media and technology applications has proven effective in reaching the community, especially the younger generation, and building collective awareness of the importance of protecting forest, coastal, and other natural resource ecosystems. However, challenges such as limited access to technology in remote areas are still obstacles to expanding the impact of this campaign. Therefore, this research recommends increasing access to technology and further collaboration between governments, NGOs, and local communities to maximize the potential of environmental communications.